CTNNB1-mutant colorectal carcinomas with immediate invasive growth: a model of interval cancers in Lynch syndrome - Ahadova, Aysel; Knebel Doeberitz, Magnus von; Kloor, Matthias (Familial cancer, 2016)
The implementation of regular colonoscopy programs has significantly decreased the mortality associated with colorectal cancer (CRC) in Lynch syndrome patients. However, interval CRCs in Lynch syndrome that remain undetected by colonoscopy still represent a substantial problem in the management of the syndrome. One possible reason of interval cancers could be a non-polypous pathway of cancer development. To examine the possibility of a non-polypous pathway of CRC development in Lynch syndrome, we analyzed the histological appearance of 46 Lynch syndrome-associated CRCs and compared them to 34 sporadic microsatellite unstable cancers. We observed that 25 (62.5 %) out of 40 assessable Lynch syndrome-associated carcinomas lacked evidence of polypous growth, compared to 17 (50 %) out of 34 sporadic MSI-H cancers. We detected CTNNB1 mutations in 8 (17.4 %) out of 46 Lynch syndrome-associated cancers compared to 0 out of 34 sporadic MSI-H cancers (p = 0.01). The majority of CTNNB1-mutant cancers presented with a histological appearance suggesting immediate invasive growth. Our results suggest that a distinct subgroup of CRCs in Lynch syndrome may in fact emerge from a non-polypous precursor, thus potentially explaining the phenomenon of interval cancers. Such a non-polypous precursor may be the recently described mismatch repair-deficient crypt focus, which remains invisible for the examiner during colonoscopy. This calls for considering the implementation of active, primary preventive measures in the management of Lynch syndrome. Future studies on pathogenic pathways and precursor lesions in Lynch syndrome are strongly encouraged, and the clinical efficacy of new prevention approaches should be evaluated in prospective clinical trials.